1991
DOI: 10.1007/bf02513556
|View full text |Cite
|
Sign up to set email alerts
|

A galling aphid with extra life‐cycle complexity: Population ecology and evolutionary considerations

Abstract: In most gall-forming aphids, only the fundatrix is able to induce a gall on the host plant. In Smynthurodes betae Westw. (and a few other species), Fz descendants emerge from the mother gall and induce their own, morphologically different galls. This constitutes an added complexity to the already very complex life cycle of gall-forming aphids.We investigated the ecology of S. betae on marked trees and shoots at four sites in Israel. Gall initiation, gall distribution and density, and temporal changes in clone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 37 publications
(39 reference statements)
1
24
1
Order By: Relevance
“…is very different from that of the other two aphid species: each clone occupies one gall on the tree. In contrast, F. riccobonii and S. betae produce two different galls on the tree host, within 2-3 weeks of each other (Wool and Burstein 1991). The first gall type is established by the fundatrix, while the second type is induced by the nymphs of her first brood.…”
Section: Discussionmentioning
confidence: 94%
“…is very different from that of the other two aphid species: each clone occupies one gall on the tree. In contrast, F. riccobonii and S. betae produce two different galls on the tree host, within 2-3 weeks of each other (Wool and Burstein 1991). The first gall type is established by the fundatrix, while the second type is induced by the nymphs of her first brood.…”
Section: Discussionmentioning
confidence: 94%
“…Some researchers suggest that there is no relationship between these variables, and that Þnal gall size is determined when the gall is induced (Wool and Manheim 1986, Wool and Burstein 1991, Wool and Bar-El 1995. By contrast, David and Ofra (1998) suggested that gall size is positively correlated with the number of aphids inside the gall; that is, large colonies live in large galls and vice versa.…”
Section: Discussionmentioning
confidence: 98%
“…Several previous studies of the in¯uence of natural enemies on aphid populations tested halfcages or open bags to determine whether these eects could be distinguished, but instead found intermediate responses between those of fully enclosed and exposed aphid populations (Campbell and Cone 1994;Chambers et al 1983;Morris 1992). In other aphid species, only the foundress generation may form galls or pseudogalls on host plants (Wool and Burstein 1991); therefore, the costs of dispersal to new leaves by the parthenogenetic generations may be very high. Way and Banks (1968) observed very little dispersal from initially colonised E. europaeus leaves in spring.…”
Section: Discussionmentioning
confidence: 99%